Nutritional Quality and Safety of Chicken Meat Consumed in Ota, Ogun State - Kayode , O.T.; Afolayan, O.A.; Kayode, A.A.A.; Mohammed, H.A. (International Journal of Poultry Science, 2018)
Background and Objective: Imported chicken meat is smuggled into the country through the porous borders of Idiroko road which leads into Ota, Ogun State and sold to retailers in the open market. This study was carried out to assess and compare the nutritional composition and safety profile of the imported frozen, exotic commercial and indigenous chicken meats consumed in Ota metropolis. Materials and Methods: A total of 21 chicken meat samples were used for the study. Group 1, 2 and 3 comprise of seven samples each of imported frozen, exotic commercial and local chicken meat, respectively. The samples were digested and nutritional composition assessed by determination of proximate composition and essential elemental analysis. The safety profile was determined by quantification of levels of heavy metals (cadmium, lead and chromium), malondialdehyde and lipid profile of the chicken meats. Data analysis was done using SPSS version 15.0. The level of significance was set at p